Prototype design and test analysis of a bean particle separating machine (2012)
The initial stages of the design, fabrication and performance analysis of a prototype beans particle-separating machine are discussed in this work. The working principle of the machine is based on the difference in aerodynamic properties as the basis for separation of beans and associated foreign particles, mainly chaff and stones. To achieve this pneumatic principle, the archetypal design necessitated the incorporation of two blower fans at various tilt angles to the horizontal plane. The results of the performance analysis of the separator showed that maximum efficiencies were 95% at 40º tilt angle for the first fan and 90% at 0º tilt angle for the second fan.